Karakterisasi Fraksi Aktif Antioksidan dari Ekstrak Etanol Biji Kemangi (Ocimum Basilicum L.) - Dede Sukandar; Sandra Hermanto; Eka Rizki Amelia; Chitta Putri Novianti (Jurnal Kimia Valensi, 2015)
Characterization of antioxidant compounds from the seeds of basil (Ocimum basilicum L.) has been done. Extraction is done by maceration method using ethanol solvent, fractionation by TLC and column chromatography, antioxidants test using DPPH method, and characterization of antioxidant compound using GCMS. Ethanol extract and results of fractionation ethanol extract of basil seeds using n-hexane, ethyl acetate, n-butanol and methanol-water extracts show that n-butanol extract has the highest antioxidant activity with IC50 values ​​of 41.90 ppm. Results of column chromatography n-butanol extract using n-hexane : ethyl acetate (1:9) as mobile phase yielded 5 fractions with fraction 4 (F4 isolate) has dominant stain of active antioxidants after being sprayed DPPH reagent, it had IC50 values ​​of 39,70 ppm and total phenolic content of 0,003 mg/g. Isolate F4 suspected contains two active compounds as antioxidant which is terpenoid and phenolic compound group, namely squalene and 1,4-di-tert-buthyl-phenol identified by GCMS.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3598